2015
DOI: 10.1007/s10973-015-4703-0
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative approach to dynamic and isothermal curing of an epoxy resin modified with oligomeric siloxanes

Abstract: The reactivity of a system comprising commercial epoxy resin Epidian Ò 6 (E6) and triethylenetetramine (Z-1) hardener was studied. The system was modified with two low-molecular siloxane modifiers: 1,3-bis(glycidyloxypropyl)-1,1,3,3-tetramethyldisiloxane (DS1) and 1,3-bis(aminopropyl)-1,1,3,3-tetramethyldisiloxane (DS2). The modifiers replaced 10 mass% of E6 or Z-1, respectively. The systems E6/DS2 and DS1/Z-1 were also studied. Enthalpy of curing was determined for all systems in isothermal conditions and dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…The shape of the observed DSC curing curve of the PETEP-CBz hybrid pre-polymer is similar to that of the DSC curing curve observed for commercial epoxy blended with benzoxazine. [42][43][44][45][46] The resulting thermogram of the PETEP-biobased benzoxazine hybrid pre-polymer shows a broad exothermic peak between 179 C and 192 C. Further, it was observed that the bio-based cardanol benzoxazine-PETEP/ polyamidoimidazoline hybrid pre-polymer shows a peak curing temperature of 185.7 C and an enthalpy of À89.78 J g À1 . The observed value of enthalpy in the present investigation is comparable with previously reported values of a commercial DGEBA/triethylenetetramine system (À95.6 to À98.3 J g À1 ).…”
Section: Thermal Behaviour Of Petep-cbz Matrix and Its Compositesmentioning
confidence: 98%
“…The shape of the observed DSC curing curve of the PETEP-CBz hybrid pre-polymer is similar to that of the DSC curing curve observed for commercial epoxy blended with benzoxazine. [42][43][44][45][46] The resulting thermogram of the PETEP-biobased benzoxazine hybrid pre-polymer shows a broad exothermic peak between 179 C and 192 C. Further, it was observed that the bio-based cardanol benzoxazine-PETEP/ polyamidoimidazoline hybrid pre-polymer shows a peak curing temperature of 185.7 C and an enthalpy of À89.78 J g À1 . The observed value of enthalpy in the present investigation is comparable with previously reported values of a commercial DGEBA/triethylenetetramine system (À95.6 to À98.3 J g À1 ).…”
Section: Thermal Behaviour Of Petep-cbz Matrix and Its Compositesmentioning
confidence: 98%
“…The kinetics of the curing reaction between epoxy and anhydride amines, oligomeric siloxanes, enzymatically hydrolyzed lignin, and in particular, nanosilica been examined well before. Barghamadi studied the kinetics of the curing reaction for nanocomposites based on bisphenol A epoxy resin (DGEBA), nanosilica, and nanoclay hardened with 4,40‐diaminoazobenzene by means of an isothermal technique of differential scanning calorimetry (DSC).…”
Section: Introductionmentioning
confidence: 99%
“…It can offer the benefits of both silicone resins and epoxy resins 20,21 as siloxane in the copolymeric form chemically bonds to the epoxy resin. There were kinds of epoxy functional siloxanes studied, such as siloxane in backbone (epoxy terminated [20][21][22][23][24][25][26][27][28][29][30][31] or grafted, 1,2,4,21,32 siloxane grafted, [32][33][34] at the presence of curing agent amine 1,21,22,24,26,27,32,33,[35][36][37] or anhydride 20,23,25,38 or other. 2,4 Characterization of the curing kinetics of the epoxy functional siloxane is one of the prerequisites for designing and optimizing the process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It can offer the benefits of both silicone resins and epoxy resins as siloxane in the copolymeric form chemically bonds to the epoxy resin. There were kinds of epoxy functional siloxanes studied, such as siloxane in backbone (epoxy terminated or grafted, siloxane grafted, at the presence of curing agent amine or anhydride or other…”
Section: Introductionmentioning
confidence: 99%